2020
DOI: 10.1002/eat.23401
|View full text |Cite
|
Sign up to set email alerts
|

The association of traumatic events and posttraumatic stress disorder with greater eating disorder and comorbid symptom severity in residential eating disorder treatment centers

Abstract: Objective: Traumatic events, posttraumatic stress disorder (PTSD) and related symptoms are commonly associated with eating disorders (ED). Several clinical features indicative of a more severe and complex course have been associated with traumatized ED patients, especially those with PTSD, who may be more likely admitted to residential treatment (RT). Research in this population is sparse but of increasing interest. Method: Adult participants (96.7% female) with EDs entering RT (n = 642) at seven sites in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 32 publications
4
49
0
1
Order By: Relevance
“…From a clinical perspective, the patients who experienced traumatic events in this study had a more impaired psychopathological profily than the others, reportingmore severe ED psychopathology and psychological symptoms and a poorer quality of life. This evidence is in line with the recent literature from various different countries that has revealed a more complex profile in patients with traumatic experiences and various EDs (Backholm et al, 2013;Brewerton et al, 2020;Longo et al, 2021), and it corroborates the evidence of a specific adverse effect of trauma with a possible specific ecophenotype for ED patients with traumatic experiences (Chami et al, 2019). We confirmed the presence of a poorer quality of life and an impaired psychosocial domain (Backholm et al, 2013;Brewerton et al, 2020) in ED patients with traumatic events, supporting the importance of evaluating traumatic history in ED patients (Brewerton, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…From a clinical perspective, the patients who experienced traumatic events in this study had a more impaired psychopathological profily than the others, reportingmore severe ED psychopathology and psychological symptoms and a poorer quality of life. This evidence is in line with the recent literature from various different countries that has revealed a more complex profile in patients with traumatic experiences and various EDs (Backholm et al, 2013;Brewerton et al, 2020;Longo et al, 2021), and it corroborates the evidence of a specific adverse effect of trauma with a possible specific ecophenotype for ED patients with traumatic experiences (Chami et al, 2019). We confirmed the presence of a poorer quality of life and an impaired psychosocial domain (Backholm et al, 2013;Brewerton et al, 2020) in ED patients with traumatic events, supporting the importance of evaluating traumatic history in ED patients (Brewerton, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The presence of trauma has a biological impact on the management of stress, with a dysregulation of the body stress response system and the development of dysfunctional responsive behaviors (e.g., impulsivity), which have a negative impact on treatment outcome (Corstorphine et al, 2007;Monteleone et al, 2015Monteleone et al, , 2020a. Traumatic events also have a negative impact on the ED patients' quality of life, increasing symptomatology and requiring specific treatments (Brewerton et al, 2020). With reference to clinical presentation, childhood sexual abuse has been correlated in EDs to multi-impulsivity, with the presence of binge-purging behaviors, substance abuse, and self-harm behaviors, while childhood physical abuse was associated with underweight (Caslini et al, 2016;Trottier and MacDonald, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Why individuals with restricting ED subtypes would be less likely to have experienced SLEs is unclear. One interpretation is that SLEs and traumas cause behaviors that are characterized by impulsivity, as many studies have found associations between SLEs and other impulsive behaviours and maladaptive coping such as suicide attempts [46] and substance abuse [47,48] in addition to the more ED specific behaviours binge eating and purging [4,10,49]. Behavioural impulsivity has also been shown to mediate the relationship between childhood abuse and binge eating and purging in non-clinical populations [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…To date, associations between SLEs and EDs are more consistent for binge-eating/purging subtypes (i.e., BN and BED) than restricting (i.e., AN) subtypes [3,4,[8][9][10][11][12]. A recent review of published risk factor metaanalyses investigating a range of risk factors found evidence for childhood sexual abuse as a risk factor for BN, while the evidence was weaker for the other ED subtypes [13].…”
Section: Introductionmentioning
confidence: 99%
“…Deve-se ressaltar que os possíveis mecanismos responsáveis pelo consumo calórico em animais não podem ser totalmente extrapolados para humanos adultos, que possuem outros fatores para desregular seu consumo calórico. Problemas de autoestima e inibição de emoções e sentimentos reduzem o consumo alimentar(VERVAET et al, 2020), enquanto que tristeza ou ansiedade estimulam seu aumento(BREWERTON et al, 2020).A maior concentração de HDL de PAE em relação a HAE pode ser apoiada estudo deJimenéz-Maldonado et al (2019), que observaram acúmulo hepático de colesterol gerado pela dieta hiperlipídica, o que inibe da expressão de ABC1 e reduz a produção de HDL. Além disso, o aumento da concentração sérica de triglicerídeos do subgrupo HAE em relação ao PAE e o aumento da quantidade de tecido adiposo do grupo H em relação ao P podem ser apoiados pelos achadosde Da Luz et al (2011), que observaram aumento da produção hepática de Lipoproteínas de Muito Baixa Densidade (VLDL) e do processo inflamatório no retículo endoplasmático (RE) causados pela dieta hiperlipídica, o que reduz a lipólise e a produção energética mitocondrial e aumenta o armazenamento de triglicerídeos no tecido adiposo.…”
unclassified